The Role of Constitutional Law in the Development of A Democratic System of Government and Social Justice in Indonesia - Diana Fitria Ayuningtyas; Rusdianto Rusdianto; Fry Anditya Rahayu Putri Rusadi (Rechtsvinding, 2026)
This study aims to analyze the role of constitutional law in building a democratic system of government and realizing social justice in Indonesia. This study uses a descriptive qualitative approach with a literature study method as a data collection technique. The data obtained are analyzed through three stages, namely data reduction, data presentation, and drawing conclusions. The focus of this study is to understand how the constitution as the basic law of the state functions to guarantee the principles of democracy and ensure the creation of equitable welfare for the entire community. The results of the study indicate that constitutional law has a crucial role in forming a democratic system of government through the principles of popular sovereignty, separation of powers, supremacy of law, and protection of human rights. The checks and balances mechanism regulated in the constitution is an important instrument in preventing abuse of power and ensuring accountability in state governance. In addition, social justice as a constitutional mandate is realized through policies that are inclusive and oriented towards the welfare of the community, especially for vulnerable groups. However, there are still challenges in the implementation of constitutional law, such as weak law enforcement, social inequality, and corrupt practices that hinder the achievement of substantial democracy and equitable social justice. Thus, efforts to improve through institutional reform, increased transparency, and public participation in policy making are important steps in strengthening the role of constitutional law in Indonesia.